Chalcogenides Metastability and Phase Change Phenomena - Kolobov, Alexander V.; Tominaga, Junji; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
A state-of-the-art description of metastability observed in chalcogenide alloys is presented with the accent on the underlying physics. A comparison is made between sulphur(selenium)-based chalcogenide glasses, where numerous photo-induced phenomena take place entirely within the amorphous phase, and tellurides where a reversible crystal-to-amorphous phase-change transformation is a major effect. Applications of metastability in devices¿optical memories and nonvolatile electronic phase-change random-access memories among others are discussed, including the latest trends. Background material essential for understanding current research in the field is also provided.
Essentials of amorphous semiconductors -- Photo-induced phenomena in S- and Se-based chalcogenides.-Metastability in Te-based chalcogenides -- Phase change in Te-based alloys for memory applications -- Phase-change optical data storage -- Super-resolution near-field sructure (Super-RENS) optical discs -- Ovonic unified memories -- What comes next.
Keywords: Optical materials; Electronic materials; Lasers; Photonics; Engineering; Optical and Electronic Materials; Optics, Lasers, Photonics, Optical Devices; Engineering, general